Mathematics Teachers’ Degree of Knowledge of Math Learning Disabilities’ Symptoms (Dyscalculia) among Students - Al-Najadat, Hussain Matrouk; Al-Farahid, Nisreen AbdelMajid (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify mathematics teachers' degree of knowledge of math learning Disabilities’ symptoms (dyscalculia) among students in the Tafila Governorate. To achieve the goal of the study, a questionnaire was developed to measure teachers' degree of knowledge of (dyscalculia). The study population consisted of (192) male and female math teachers in government schools in the Tafila and Bosaira educational districts. The results of the study indicated that teachers' degree of knowledge was at the mild level. The results indicated that 16% of teachers have a high degree of knowledge, 70% have a medium degree, and 14% have a low degree. The results also showed significant differences in math teachers' average degree of knowledge in identifying the symptoms of math learning disabilities according to their gender, academic qualification, and experience. Finally, the study recommended professional development programs for teachers that include diagnostic methods and techniques that enable them to identify the symptoms of dyscalculia among students accurately.
Keywords: Dyscalculia; Mathematics Teachers; Learning Disabilities’ Symptoms